Factors affecting fruit and vegetable consumer behaviour among adults in Sub-Saharan Africa: A rapid review - Stadlmayr, B.; Trübswasser, Ursula; McMullin, S.; Karanja, A.; Wurzinger, Maria; Hundscheid, L.; Riefler, P.; Brouwer, Inge D.; Sommer, I. (2021)
The aim of this rapid review is to assess and synthesise data on individual, social, physical and macro-level factors that affect consumption and purchase of fruit and vegetables, to identify gaps and to guide future research.